Performance appraisal system: a case study on Riverview Rubber Estate Bhd / Nur Shaharwani Anuar - Anuar, Nur Shaharwani (Faculty of Business and Management, 2010)
Implementation of performance appraisal on employee work performance and subsequently the derived feedback and effects to the management of an organization. However the pervasive practice of Performance Appraisal will giving problems to the organization. Performance appraisal is perceived to be a critical human resource management function in Riverview Rubber Estates Bhd. This case study will explore the potential benefits and problems associated with performance appraisal in Riverview Rubber Estates Bhd and discuss ways to improve this pervasive practice. This thesis tried to review the attitude of employees to work as a result of performance appraisal within an organization and to review the effects of performance appraisal on employee work performance and work effectiveness. The primary data for this work was collected from the interview received from the employees of Riveview Rubber Estates Berhad and also secondary data was collected from journals and other research works. There have been positive changes in the attitude of employees towards work and the organization as a whole, as a result from performance appraisal system. Performance appraisal system also leads to the job specialization which as the staff performs the job in year out the performance appraisal results serve as a guide to them on which areas should be improves, All these are noticeable in this case study. An effective performance appraisal systems help to create a motivated and committed workforce. To be effective they require the support of top management to show their commitment and to translate organizational goals and objectives and requires strong commitment from both party employees and top management. Implementation of performance appraisal need an appropriate training for supervisors, raters and employees. Performance appraisal feedback should be performed frequently to help build the direct communication link between employer and employee.